Pembentukan Karakter Melalui Strategi Belajar Aktif dalam Proyek P5RA Bertema Sayuran - Diyah Andini Kusumastuti; Muhlisin Muhlisin; Abdul Khobir (Badan Penerbit STIEPARI Press, 2025)
The problem of the character of students at the basic education level such as madrasah ibtidaiyah is a serious challenge in the world of education today. The phenomenon of declining attitudes of discipline, responsibility, social concern, and rampant impolite behavior towards teachers and parents are indicators of the importance of building strong character. This study aims to examine the application of active learning strategies in the Pancasila and Rahmatan Lil Alamin (P5RA) Student Profile Strengthening project with the theme Sayuranku Sahabat Sehatku as an effort to shape the character of students. This study uses a qualitative descriptive approach with the systematic literature review (SLR) method on various relevant sources. The results of the study show that the application of active learning strategies through planting and caring for vegetables directly is able to instill character values such as responsibility, cooperation, religiosity, and concern for the environment. Active learning strategies allow students to be directly involved in the process of planning, implementing, and reflecting on learning, resulting in meaningful and contextual learning. Project based learning in P5RA activities has also proven to be effective in integrating the values of Pancasila and Islam Rahmatan Lil Alamin, making it the right means to shape the character of students as a whole.